Micro-geographic variation in antigenic diversity of PfEBA-175 region II in asymptomatic Plasmodium falciparum infections in Tanzania - Syahada, Jadidan Hada; Lee, Wang-Jong; Jun, Hojong; Louis, Johnsy Mary; Fitriana, Fadhila; Muh, Fauzi; Lu, Feng; Ahmed, Md Atique; Na, Sunghun; Chun, Wanjoo; Park, Won Sun; Jeon, Bo-Young; et al. (Frontiers in Immunology, 2025)
BackgroundMalaria remains a major public health burden, and the development of effective blood-stage vaccines is complicated by extensive antigenic variation in Plasmodium falciparum antigens. PfEBA-175, a leading vaccine candidate, mediates erythrocyte invasion by binding to glycophorin A via its region II (RII), which is known to be highly polymorphic.MethodsWe examined the genetic diversity and antigenicity of PfEBA-175 region II (RII) in 172 asymptomatic P. falciparum isolates collected from Geita and Kigoma, Tanzania. Sequence diversity was assessed through nucleotide diversity (π) and analysis of selection pressure using dN-dS and Fu’s Fs tests. A recombinant PfEBA-175 RII protein was expressed to evaluate antibody response in plasma samples.ResultsSequence analysis revealed high nucleotide diversity (π = 0.00359 ± 0.00012), with evidence of adaptive evolution driven by immune pressure (dN-dS = 3.15, p < 0.001), and sign of recent population expansion based on Fu’s Fs value (-30.614). A recombinant RII protein exhibited high antigenicity, with an average seropositivity of 84.8%, although rates varied across villages, ranging from 95.4% in Rwantaba to 50.0% in Bunyambo. The antibody response was positively correlated with age (ρ = 0.333, p < 0.001), but not with parasitemia or gender. Several important amino acids substitutions, including K478N, K481I, and L482V, were located within B-cell epitopes targeted by the invasion-inhibitory monoclonal antibody R217, and N577K, found at the dimer interface, had little effect on naturally acquired immune responses. However, several charged amino acid substitutions including D168H, T198K, K275I, K448N, and D619H influenced natural acquired antibody recognition.ConclusionDespite substantial polymorphism, the glycan-binding residues of PfEBA-175 RII remain conserved, and its high antigenicity across diverse geographic and demographic contexts supports its continued evaluation as a blood-stage vaccine candidate. These findings highlight the importance of accounting for naturally occurring antigenic variation in malaria vaccine development.